The Role of Digital Marketing Transformation Trends on Purchase Intention - Aji Prasojo; Sudarmiatin Sudarmiatin (Global Leadership Organizational Research in Management, 2024)
Media marketing channels are developing very rapidly in the current era. Conventional marketing is becoming digital marketing, a good innovation in promoting a product or service. To win competition in the era of digital transformation, business people must be able to adapt. One digital marketing strategy is a promising option and has the opportunity to reach a wider market. The research was conducted on Instagram @osaka_organizer. This research aims to find out how the role of digital marketing can increase purchasing interest. This research uses a qualitative descriptive method involving direct observation and interviews. Studies show that Osaka Organizers' digital marketing strategy to increase consumer buying interest via Instagram has a positive impact.